Evaluation of the immunogenicity of an mRNA vectored Nipah virus vaccine candidate in pigs - Pedrera, Miriam; McLean, Rebecca K.; Medfai, Lobna; Thakur, Nazia; Todd, Shawn; Marsh, Glenn; Bailey, Dalan; Donofrio, Gaetano; Muramatsu, Hiromi; Pardi, Norbert; Weissman, Drew; Graham, Simon P. (Frontiers in Immunology, 2024)
Nipah virus (NiV) poses a significant threat to human and livestock populations across South and Southeast Asia. Vaccines are required to reduce the risk and impact of spillover infection events. Pigs can act as an intermediate amplifying host for NiV and, separately, provide a preclinical model for evaluating human vaccine candidate immunogenicity. The aim of this study was therefore to evaluate the immunogenicity of an mRNA vectored NiV vaccine candidate in pigs. Pigs were immunized twice with 100 μg nucleoside-modified mRNA vaccine encoding soluble G glycoprotein from the Malaysia strain of NiV, formulated in lipid nanoparticles. Potent antigen-binding and virus neutralizing antibodies were detected in serum following the booster immunization. Antibody responses effectively neutralized both the Malaysia and Bangladesh strains of NiV but showed limited neutralization of the related (about 80% amino acid sequence identity for G) Hendra virus. Antibodies were also capable of neutralizing NiV glycoprotein mediated cell-cell fusion. NiV G-specific T cell cytokine responses were also measurable following the booster immunization with evidence for induction of both CD4 and CD8 T cell responses. These data support the further evaluation of mRNA vectored NiV G as a vaccine for both pigs and humans.